Disruption of FGF Signaling Ameliorates Inflammatory Response in Hepatic Stellate Cells - Wang, Cong; Li, Yuelong; Li, Hao; Zhang, Yali; Ying, Zhangguo; Wang, Xuye; Zhang, Tingting; Zhang, Wenshu; Fan, Zhichao; Li, Xiaokun; Ma, Jisheng; Pan, Xuebo (Frontiers in Cell and Developmental Biology, 2020)
It is a well-documented event that fibroblast growth factors (FGFs) regulate liver development and homeostasis in autocrine, paracrine, and endocrine manners via binding and activating FGF receptors (FGFRs) tyrosine kinase in hepatocytes. Recent research reveals that hepatic stellate cells (HSCs) play a fundamental role in liver immunology. However, how FGF signaling in HSCs regulates liver inflammation remains unclear. Here, we report that FGF promoted NF-κB signaling, an inflammatory pathway, in human HSCs, which was associated with FGFR1 expression. Both FGF and NF-κB signaling in HSCs were compromised by FGFR1 tyrosine kinase inhibitor. After stimulating HSCs with proinflammatory cytokines, expression of multiple FGF ligands was significantly increased. However, disruption of FGF signaling with FGFR inhibitors prominently reduced the apoptosis, inflammatory response, NF-κB nuclear translocation, and expression of matrix metalloproteinase-9 (MMP-9) induced by TNFα in HSCs. Interestingly, FGF21 significantly alleviated the inflammation responses in the concanavalin A (Con A)-induced acutely injured liver. Unlike canonic FGFs that elicit signals through activating the FGFR–heparan sulfate complex, FGF21 activates the FGFR–KLB complex and elicits a different set of signals. Therefore, the finding here indicates the urgency of developing pathway-specific inhibitors that only suppress canonical FGF, but not non-canonical FGF21, signaling for alleviating inflammation in the liver, which is presented in all stages of diseased liver.